A model of aid and Dutch Disease in Sub-Saharan Africa - David Fielding; Fred Gibson (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2012)
International aid has an ambiguous effect on the macro-economy of the recipient country. To the extent that aid raises consumer expenditure, there will be some real exchange rate appreciation and a shift of resources away from traded goods production and into non-traded goods production. However, aid for investment in the traded goods sector can mitigate this effect. Also, a relatively high level of productivity in the non-traded goods sector combined with a high level of investment will tend to depreciate the real exchange rate. We examine aid inflows in 26 Sub-Saharan African countries, and find a variety of macro-economic responses. Some of the variation in the responses can be explained by variation in observable country characteristics; this has implications for donor policy.
Keywords: F41; O56; 330; Aid; Dutch Disease; Africa